Multimorbidity and Health Care Service Utilization in the Australian Workforce: Findings From the National Health Survey. Issue 8 (August 2017) - Wang, Lili; Palmer, Andrew J.; Otahal, Petr; Cocker, Fiona; Sanderson, Kristy
Abstract : Objectives: The aim of this study was to understand the patterns of health care service utilization in employees with multimorbidity. Methods: Data were obtained from the 2011 to 2012 cross-sectional Australian National Health Survey. Past-month health care service utilization was collected for each chronic condition from a pre-specified list. Descriptive, logistic, and Poisson regression analyses were used. The data were weighted to produce nationally representative estimates. Results: Multimorbid employees with arthritis had higher adjusted arthritis-specific general practitioner (GP) visit rates [rate ratio (RR) = 1.7, 95% confidence interval (95% CI) = 1.1 to 2.2, P < 0.001] than employees with arthritis alone. Similarly, multimorbid employees with cardiovascular disease (CVD) had higher adjusted CVD-specific specialist visit rates (RR = 1.6, 95% CI = 1.1 to 2.5, P < 0.05) and 2.5 times (95% CI = 1.5 to 4.0, P < 0.001) more CVD-specific other health professional visits than employees with CVD alone. Conclusions: Given the increasing number of employees managing work and chronic illnesses, these findings have implications for health services and employers.